ANALYSIS OF EXPORT AND IMPORT ACTIVITIES IN PT. BUANA MAS CITRA LESTARI - Jessen Yap, Farina; Manalu, Pius Deski (PT. MITRA ANGKASA INFORMATIKA, 2024)
The very rapid development of business in the world has led to the emergence of international trade which is divided into two types, namely exports and imports. Realizing the importance of export and import activities, it was found that there are many roles that carry out the flow, one of which is the role of freight forwarding such as PT. Buana Mas Citra Lestari. Researchers formulate the problem in this research into a documentation and cost determination process at PT. Buana Mas Citra Lestari. The method used in this research is a qualitative approach, then the type of this research is descriptive qualitative and the nature of this research is explanatory research. The population in this study was PT. Buana Mas Citra Lestari Medan branch, which was founded in 2010, and samples consist of documents and costs for the period July 2018 – July 2019. Data collection methods were carried out using observation techniques, documentation study techniques, interview techniques, and library study techniques. The research results show that there are imperfections in documentation and cost determination at PT. Buana Mas Citra Lestari Medan caused by the lack of computerization and management systems in place.